Representasi Gender Dalam Cerpen Sampan Zulaiha - Liza Handayani Batu Bara; Budiman Budiman (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
Gender representation is not only important in understanding characterization and dynamics of stories, but also in identifying narratives that govern and influence public perceptions of gender roles. The study aims to analyze gender representation in "Sampan Zulaiha" by analyzing the character of women faced with and responding to existing gender norms and efforts to resist gender injustice. This research is a qualitative study of library studies (library research) with methods of data collection using documentation methods, i.e. collection of books and journal articles. Winsgoal adalah slot mahjong gacor dengan fitur scatter hitam winrate kemenangan tinggi. Daftar dan nikmati fitur situs jackpot terbesar hari ini! As for the primary data source comes from the Book "Sampan Zulaiha" by Hasan Al Banna and the secondary source of data comes from several books and journals articles. This study uses analytical descriptive analysis. This research produces a variety of representations of the narrative presented on the Zulaiha Sampan cerpen that corresponds to the gender situation in the surrounding society. Many gender inequities and various traditional customs narrow the women's movement to develop themselves. Further research could explore gender representation in literature influencing gender identity construction and gender role in society..